Pengaruh Perawatan Payudara Dengan Kejadian Bendungan Asi Pada Ibu Post Partum Di Puskesmas Tampojung Pregi - Rohimah; Lea ingne Reffita (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
Breast care is a way of treating breast is done when the pregnancy or during childbirth to facilitate milk production, in addition to the breast hygine and for nipple shape that is entered into or horizontal . and a good Breast care to have an important role in improving milk production and avoid the dangers of the dam breast milk of mothers. The purpose of this study is to know the relationship a breast care with dam breast milk insident in mothers post partum.The design of this study was cross-sectional analytic types. The population is all postpartum women, who has experiences about dam breast milk samples were 20 respondents. Sampling techniques using simple random sampling using the chi squers test. Measuring instruments using questionnaires and observation. Independent variable is the variable dependenya breast care and breast milk is the dam on postpartum mothers.Based on the statistical test using contingency coeficient obtained values ​​for sig count 0,012 0,012 <0.05, then reject Ho and accept H1. This means that there is a correlation with the incidence of breast care dam postpartum breastfeeding mothers.Efforts to resolve the problem is with the increase in education and health promotion efforts more intensively by health workers either to individuals or groups.